Negotiating Anthropocentrism and Ecologies in Cozy Games - Pinder, Morgan (Replay. The Polish Journal of Game Studies, 2024)
As we sit at the precipice of this planet’s sixth mass extinction event, we need to use every tool at our disposal to advocate for our ecologies. Human self-interest and anthropocentric thinking act as barriers to communicating ecocrisis. Cozy video games can create safe spaces to explore the ecological effects of human actions with the aim of prompting reflection and action on environmental issues. Drawing on ecocritical video game scholarship, the aim of this article is to explore the ways in which environments are represented and interacted with in selected cozy video games. Through an examination of the extractivist colonial processes and narratives of Animal Crossing: New Horizons, in contrast with the complex ecocritical coziness of Terra Nil, this article posits that cozy games have the potential to achieve effective environmental communication. Both Animal Crossing: New Horizons and Terra Nil successfully empower the player to shape their environment but only Terra Nil affords ecological empowerment. By creating a safe space to engage with environments and even ecocrisis, cozy games allow players the agency to construct their own econarratives and may challenge or perpetuate anthropocentric ideas about the environment.